Immune response to hepatitis B vaccine following complete immunization of children attending two regional hospitals in the Southwest region of Cameroon: a cross sectional study - Ephesians N. Anutebeh (BMC, 2021)
Abstract Background Hepatitis B virus (HBV) infection despite being a vaccine preventable disease remains a global public health problem. In Cameroon, the hepatitis B vaccine was introduced in the expanded program on immunisation in 2005, but there has been limited evaluation of the HBV surface antibody response post vaccination. Objective We investigated the immune response to hepatitis B vaccine in infants who received the DPT-Hep B-Hib vaccine, and we assessed HBsAg carriage in non-responders. We also investigated factors associated with non-response or poor response. Methods Using a hospital based cross sectional design and a structured questionnaire over a four-month period (January to April 2019), we collected data to determine factors associated with hepatitis B surface antibody (anti-HBs) response from infants aged 6 to 9 months attending infant welfare clinics (IWC) at the Buea and Limbe regional hospitals. We collected venous blood and measured anti-HBs titres using a quantitative Foresight® ELISA. We entered and analysed data using EpiData version 3.1 and SPSS version 25 respectively. Results Of the 161 infants enrolled, 159 (98.8%) developed anti-HBs antibodies. Of these 159, 157 (97.5%) and 117 (72.7%) developed ≥ 10.0 mIU/ml (seroprotection) and ≥ 100.0 mIU/ml anti-HBs titres respectively. Being younger (6 months old) was associated with seroprotection (Cramer V = 0.322, p = 0.001). Spearman rho’s relational analysis showed that immunity against HBV reduced as the duration since the last dose increased (r = −0.172; P = 0.029). However, a Firth logistic regression showed no significant association of factors with inadequate immunity. All 12 (7.5%) infants exposed to HBV at birth, received the hepatitis B vaccine at birth, including four who received HBIG, and all were protected. Four infants (2.5%) had anti-HBs titres < 10.0 mIU/mL (non-responders) but had no peculiarity. Conclusion The seroprotective rate following hepatitis B vaccination of infants is high even in exposed infants. Our study suggests that Cameroon’s HBV vaccine in the Expanded Program on Immunisation (EPI) is effective against HBV, although we could not account for the 2.5% non-response rate. Large scale studies are needed to further explore non-response to the vaccine.